Hydroxyl Derivatives of Oils from Solid Fats as Components for Production of Polyurethane Foams - Elżbieta Malewska; Maria Kurańska; Klara Grelowska; Aleksandra Put; Hubert Ożóg; Julia Sędzimir; Natalia Kowalik; Michał Kucała; Aleksander Prociak (Molecules)
Biopolyols derived from solid fats of both vegetable origin (coconut oil (P/CO) and palm oil (P/PA)) and animal origin (pork fat (P/PO) and duck fat (P/DU)) were used to produce thermal insulation polyurethane foams. The biopolyols were characterized by hydroxyl numbers in the range of 341–396 mgKOH/g, a viscosity of 60–88 mPa·s, and a functionality of 2.3–3.4. Open-cell polyurethane foams were obtained by replacing from 50 to 100 wt.% of a petrochemical polyol with the biopolyols from solid fats. The most advantageous properties were found for the materials modified with the biopolyol based on pork fat, which was attributed to its high degree of cell openness. At a low apparent density, the foam materials were characterized by good dimensional stability. The use of solid fats offers new possibilities for modifying thermal insulation polyurethane foams.